Integrated Human Resource, Marketing, and Financial Management Practices and Business Performance: Evidence from Tourism Enterprises in Bali - Suastama, Ida Bagus Radendra; Wimpascima , Ida Bagus Ngurah (Forum Manajemen, 2025)
Tourism enterprises in Bali operate in a highly competitive and volatile environment that demands coordinated management across human resource, marketing, and financial functions (Sanjaya et al., 2024; Provincial Government of Bali, 2023). This study examines the effect of integrated human resource management (HRM), marketing management, and financial management practices on perceived business performance among tourism enterprises in Bali. A quantitative survey was conducted with employees and middle managers working in hotels and travel-related businesses across major tourism areas, and data were analyzed using multiple regression. The results show that HRM and marketing practices have strong positive and significant effects on perceived business performance, while financial management practices also contribute positively but with a smaller effect size. The study offers novelty by empirically testing a multidisciplinary model that combines HR, marketing, and financial practices in one framework within the Bali tourism context, and it provides practical implications for managers and policymakers to enhance cross-functional alignment in the sector (Ganie & Dar, 2020; Hermawati, 2024).   Perusahaan pariwisata di Bali beroperasi dalam lingkungan yang sangat kompetitif dan tidak stabil, yang menuntut pengelolaan terkoordinasi di berbagai fungsi, termasuk sumber daya manusia, pemasaran, dan keuangan (Sanjaya dkk., 2024; Pemerintah Provinsi Bali, 2023). Studi ini menganalisis dampak praktik pengelolaan sumber daya manusia terintegrasi (HRM), pengelolaan pemasaran, dan pengelolaan keuangan terhadap kinerja bisnis yang dirasakan oleh perusahaan pariwisata di Bali. Survei kuantitatif dilakukan terhadap karyawan dan manajer menengah yang bekerja di hotel dan bisnis terkait pariwisata di kawasan pariwisata utama, dan data dianalisis menggunakan regresi berganda. Hasil menunjukkan bahwa praktik HRM dan pemasaran memiliki dampak positif yang kuat dan signifikan terhadap kinerja bisnis yang dirasakan, sementara praktik manajemen keuangan juga berkontribusi positif tetapi dengan ukuran efek yang lebih kecil. Studi ini menawarkan keunikan dengan menguji secara empiris model multidisiplin yang menggabungkan praktik SDM, pemasaran, dan keuangan dalam satu kerangka kerja dalam konteks pariwisata Bali, dan memberikan implikasi praktis bagi manajer dan pembuat kebijakan untuk meningkatkan keselarasan lintas fungsi di sektor ini (Ganie & Dar, 2020; Hermawati, 2024).